Colonial Rivalry on the Chad-Sudan Border 1898-1924 (Faculty of Education Scientific Journal, 2024)
This study delves into the colonial competition between France and Britain for dominance in Chad and Sudan during the late 19th and early 20th centuries. The border region became a focal point for their imperial ambitions and the control of strategic resources. French expansion began in the late 1880s with the establishment of military outposts in southern Chad. Their 1898 treaty with the Sultan of Wadai formalized its status as a French protectorate, directly challenging British aspirations to extend control across all of Sudan, particularly its western regions. Throughout this study, we will explore the key events and outcomes of this colonial rivalry.
Keywords: Border disputes; Wadai Sultanate; Darfur Sultanate; Chad